Metodologias ativas no ensino de física: instrução por pares e aplicativo plickers na abordagem da unidade energia mecânica - Ribeiro, Jose Adriano de Araujo (2024)
The use of active methodologies in education as a whole has been a practice in constant evolution, especially after the long and challenging experience of the pandemic, and its impacts on the teaching and learning of teachers and students around the world. In Brazil, it was no different, and the post-pandemic scenario has increasingly demanded improvement and teacher training in the face of new and constant teaching challenges. In this context, the theme was defined: "Active Methodologies in Physics Teaching: Peer Instruction and Plickers Application in the Mechanical Energy Unit Approach", which had as its main objective to contribute to the continued training of teachers in the state public education network, with regard to the application of active learning methodologies; presenting the educational product proposal so that it can be taken forward in Physics teaching, through its application in the classroom, and the dissemination and sharing of results The study was conducted in a high school, with the participation of teachers and students in the first year of high school. The research was divided into two stages: in the first, teachers participated in a workshop applied during a training period, which addressed the active methodology of peer instruction in Physics teaching and how the Plickers application can contribute to working with content. of this discipline.In the second stage, this proposal was applied in the classroom, where students participated in a didactic sequence, divided into two moments: In the first, classes were taught without using the active peer instruction methodology on the concept of Mechanical Energy, in the second, classes were taught using the active Peer Instruction methodology and the use of the Plickers application for interaction and evaluation. The results demonstrate that students submitted to the active methodology achieved superior performance in understanding the concepts studied, compared to those who had classes taught without using the active peer instruction methodology. Furthermore, the research showed greater student engagement and interest during the activities, promoting a more participatory and collaborative learning environment. The use of active methodologies, such as Peer Instruction, with the aid of tools such as the Plickers application, represents an effective approach to teaching Physics, facilitating the understanding and application of Mechanical Energy concepts, in addition to promoting an environment of more engaging learning. The results suggest the importance of incorporating these innovative approaches into the educational curriculum, improving the quality of Physics teaching and student performance.